Roadmap on specialty optical fibers - Mário F S Ferreira; Mohd Rehan; Vishwatosh Mishra; Shailendra Kumar Varshney; Francesco Poletti; Nguyen Phuoc Trung Hoa; Weichao Wang; Qinyuan Zhang; Wenyu Du; Benli Yu; Zhijia Hu; Xian Feng; et al. (JPhys Photonics)
Optical fibers, long an enabling technology for telecommunications, are proving to play a central role in a growing number of modern applications, starting from high speed broad band internet to medical surgery and entering across the entire spectrum of scientific, military, industrial and commercial applications. Specialty optical fibers either special waveguide structure or novel material composition becomes heart of all fiber based advanced photonics devices and components. This rapidly evolving field calls on the expertise and skills of a broad set of different disciplines: materials science, ceramic engineering, optics, electrical engineering, physics, polymer chemistry, and several others. This roadmap on specialty optical fibers addresses different technologies and application areas. It is constituted by fourteen contributions authored by world-leading experts, providing insight into the current state-of-the-art and the challenges their respective fields face. Some articles address the area of multimode fibers, including the nonlinear effects occurring in them. Several other articles are dedicated to doped, plastic, and soft-glass fibers. Large mode area fibers, hollow-core fibers, and nanostructured fibers are also described in different sections. The use of some of such fibers for optical amplification and to realize several kinds of optical sources—including lasers, single photon sources and supercontinuum sources—is described in some other sections. Different approaches to satisfy applications at visible, infrared and terahertz spectra regions are also discussed. Throughout the roadmap there is an attempt to foresee and to suggest future directions in this particularly dynamic area of optical fiber technology.